DHEA and frontal fibrosing alopecia: molecular and physiopathological mechanisms - Neide Kalil Gaspar (Sociedade Brasileira de Dermatologia, 2016)
Abstract The transforming growth factor-beta 1 (TGFβ1) promotes fibrosis, differentiating epithelial cells and quiescent fibroblasts into myofibroblasts and increasing expression of extracellular matrix. Recent investigations have shown that PPAR (peroxisome proliferator-activated receptor*) is a negative regulator of fibrotic events induced by TGFβ1. Dehydroepiandrosterone (DHEA) is an immunomodulatory hormone essential for PPAR functions, and is reduced in some processes characterized by fibrosis. Although scarring alopecia characteristically develops in the female biological period in which occurs decreased production of DHEA, there are no data in the literature relating its reduction to fibrogenic process of this condition. This article aims to review the fibrogenic activity of TGFβ1, its control by PPAR and its relation with DHEA in the frontal fibrosing alopecia.